Socioemotional Development with Equine Therapy Activities. Analysis of Experiences of Children with Different Abilities - Venegas-Mejía, Clotilde Paula; Arguedas Pérez, Giulianno Mitchel; Alvarez Niño de Guzmán, Yanet; Gallegos-Espinoza, Djamila; Esquivel-Grados, José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of the study was oriented to analyze the socio-emotional development of children with different abilities who participated in equine therapy activities in the city of Lima. The study sample, carried out with a phenomenological design, was made up of parents who participated in the implementation of equine therapy activities and offered information on their children with autism, Down syndrome or attention deficit disorder with and no hyperactivity. The data collection used a questionnaire of open questions that focused on the social and emotional areas of child development, which was administered to 25 informants, a number that was reached by saturation. It was found as a result that children who participate in equine therapy activities with a holistic approach favor their socio-emotional development, referring to the attachment relationship and control of emotions in the emotional area, and communicative and interpersonal relationships. in the social área.